Island ancient genomes reveal dynamic populations interactions in the northern China - Zhang, Xu; Zhang, Fan (Frontiers in Microbiology, 2025)
The Longshan period (2500–1900 BC) was a transformative era in central China, marked by the emergence of complex social structures and early state formation. While human mobility likely played a role in these developments, the scale and nature of migration during this period remain poorly understood. Previous ancient DNA studies on Longshan culture populations have focused on individuals from inland Shandong, with no ancient DNA data available from island populations. In this study, we present the first ancient DNA analysis from individuals associated with the Longshan and subsequent Yueshi cultures on the Tuoji Island. Our findings indicate that, despite the widespread cultural influence of the inland Longshan culture in Shandong, the genetic ancestry of the Tuoji Island individuals primarily reflects connections to the preceding Dawenkou culture, with additional ancestry linked to the coastal regions of southern China. This suggests an earlier population movement into Tuoji Island before the Longshan period. However, during the Longshan period, the spread of Longshan cultural materials on Tuoji Island appears to represent the diffusion of ideas rather than significant population admixture from the inland. Additionally, our study shows genetic continuity of Longshan and Yueshi cultures in Tuoji Island highlighting the dynamic nature of coastal migration, as the Tuoji Island populations exhibit more genetic influence from coastal regions than from the inland. In contrast, inland populations during the Longshan period show no significant genetic influx from neighboring regions. This study not only advances our understanding of the prehistoric populations in Neolithic China but also provides new insights into patterns of migration and cultural exchange during this critical period.